Increasing Literacy Rates and Life Skills of Marginal Communities in Jayawijaya through Integration of Non-Formal Education PKBM and Vocational Schools: Literature Review - Wantik, Laorens Wantik; Bambang Shergi Laksono; Lefaan, Avelinus Lefaan; Lumintang, Onnie M. Lumintang (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to explore the integration between non-formal education provided by Community Learning Activity Centers (PKBM) and vocational education in Vocational High Schools (SMK) in improving literacy levels and life skills of marginalized communities in Jayawijaya. The research methods used include a systematic literature review and field studies, and involve various stakeholders, including local governments and local communities. The results show that the integration of PKBM and SMK significantly contributes to improving basic literacy and life skills, especially in agriculture and handicrafts, which are relevant to local economic needs. In addition, this education program is able to overcome the limitations of access to formal education in remote areas. Policy implications emphasize the importance of cross-sector collaboration and improving education infrastructure in supporting the sustainability of this program. This study provides recommendations for the development of more adaptive education policies in other remote areas in Indonesia.